Renegater Nils Flyg och Sven Olov Lindholm i gränslandet mellan kommunism och nazism - Stenfeldt, Johan (Kriterium, 2019)
"This study focuses on two Swedish politicians, Nils Flyg and Sven Olov Lindholm. During the interwar era, they were both leaders of various Swedish political parties; in the case of Flyg the Swedish Communist Party, and later on the Socialist Party; in the case of Lindholm the National Socialist Worker's Party (later renamed Swedish Socialist Unity). Both men were, in other words, influential politicians located at the outer edges of the ideological landscape. During the span of their lifetimes, however, Flyg as well as Lindholm made remarkable ideological transitions. From the end of the thirties and onwards, the former communist leader Flyg successively embraced German Nazism. Lindholm on the other hand stepped down from his leadership after the war, and became a left-wing political activist who did not hesitate to identify himself as a communist. Superficially, this is strikingly symmetric: The communist leader becomes a Nazi, and the Nazi leader becomes a communist. The aim of the study is to analyze the ideological links and tensions between Nazism and communism using these parallel biographies as a point of entrance. Inspired by political theorist Michael Freeden and his conceptual approach, and using a variety of sources, two core clusters of political concepts are identified and compared. It is shown that there are great similarities between Flyg and Lindholm when it comes to the role of anti-capitalism, anti-imperialism and the aspiration to idealize the Soviet Union or Germany as model states for workers. There are also, however, a number of differences, especially when it comes to views on modernity and materialism. In the final chapter, Flyg and Lindholm are compared to other European renegades. Here, the ambition is to identify common traits in the conversions. It is argued that the ideological antagonisms, the anti-positions, are crucial to this kind of generic renegadism."